Visceral and subcutaneous fat have different origins and evidence supports a mesothelial source - Chau, You-Ying; Bandiera, Roberto; Serrels, Alan; Martínez-Estrada, Ofelia M.; Qing, Wei; Lee, Martin; Slight, Joan; Thornburn, Anna; Berry, Rachel; McHaffie, Sophie; Stimson, Roland H.; Walker, Brian R.; et al. (Nature cell biology, 2014)
Increased visceral adipose tissue has been associated with metabolic dysfunction but the origin of the progenitors that give rise to this tissue, and whether they are the same as the progenitors contributing to the protective subcutaneous adipose tissue, was unclear. Hastie and colleagues have found that Wt1-positive mesothelial cells contribute to visceral adipocytes. Fuelled by the obesity epidemic, there is considerable interest in the developmental origins of white adipose tissue (WAT) and the stem and progenitor cells from which it arises. Whereas increased visceral fat mass is associated with metabolic dysfunction, increased subcutaneous WAT is protective. There are six visceral fat depots: perirenal, gonadal, epicardial, retroperitoneal, omental and mesenteric, and it is a subject of much debate whether these have a common developmental origin and whether this differs from that for subcutaneous WAT. Here we show that all six visceral WAT depots receive a significant contribution from cells expressing Wt1 late in gestation. Conversely, no subcutaneous WAT or brown adipose tissue arises from Wt1-expressing cells. Postnatally, a subset of visceral WAT continues to arise from Wt1-expressing cells, consistent with the finding that Wt1 marks a proportion of cell populations enriched in WAT progenitors. We show that all visceral fat depots have a mesothelial layer like the visceral organs with which they are associated, and provide several lines of evidence that Wt1-expressing mesothelium can produce adipocytes. These results reveal a major ontogenetic difference between visceral and subcutaneous WAT, and pinpoint the lateral plate mesoderm as a major source of visceral WAT. They also support the notion that visceral WAT progenitors are heterogeneous, and suggest that mesothelium is a source of adipocytes.